PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. CABANG TUANKU TAMBUSAI PEKANBARU - Indra Yulis; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Bank represent body of effort having important role in economics an state. Especial Aktifity of banking is muster fund from society and channel it return in the form of credit to individual or socialize, other small industry and company used to support process take place a business or commerce which its final purpose to get advantage which later will have an effect on to improvement of level live people in general. leadership of Transformasional defined by as leadership including effort of organizational change. This leadership is believed will aim at performance of superior in organization which is facing change demand. Organizational comitment employees represent important factor in company, because can have an effect on to behavior of which deal with work which are positive, for example high performance, loyalitas employees, and low turnover. high comitment from a employees of have correlation to lowly it him move job, deductible lethargy, lower nya mount out of work, and improve satisfaction work. Equally, organizational commitment a employees can give positive impact in creating environment of job which save. Organizational therefore or the company have to own mechanism to develop organizational commitment among its member.This research is done/conducted at Branch Office of Bank Rakyat Indonesia at Tuanku Tambusai Pekanbaru. Target of this Research is done/conducted to know influence of leadership of transformasional to organizational commitment.In this research is methodologies used by is quantitative and descriptive with program SPSS, where sampel used by that is employees at research object. To determine sampel use technics of census, Technics data by collecting through, observation and quesioner.From result analyse data covering validity test, reabilitas, and linear regresi sederhana, transformasional leadership have an effect on to organizational commitment. Each owning indicator which each other be interconnected and have an effect on positive to organizational commitment at Bank BRI Pekanbaru.Keyword : Style Leadership, PT. BRI, and Organization